2015
DOI: 10.1186/s12936-015-0989-4
|View full text |Cite
|
Sign up to set email alerts
|

Larval ecology of Anopheles coluzzii in Cape Coast, Ghana: water quality, nature of habitat and implication for larval control

Abstract: BackgroundThere is a growing interest in larval control intervention to supplement existing malaria control strategies, particularly in urban areas. However, effective implementation requires a good understanding of habitat ecology of Anopheles mosquitoes. Clean water bodies have long been reported by several studies as a preferred breeding habitat for Anopheles gambiae. Other studies have also reported the breeding of An. gambiae in polluted water bodies. However, the term clean or polluted is mostly based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 28 publications
12
44
0
Order By: Relevance
“…Our results confirm that Ae. aegypti does not breed only in clear water, as it can breed in containers with high turbidity (> 133 FNU), high DCO (> 242 mg/L) and low dissolved oxygen, nearly reaching anoxia, like Culex quinquefasciatus mosquitoes [53]. These findings are consistent with reports of successful Ae.…”
Section: Discussionsupporting
confidence: 88%
“…Our results confirm that Ae. aegypti does not breed only in clear water, as it can breed in containers with high turbidity (> 133 FNU), high DCO (> 242 mg/L) and low dissolved oxygen, nearly reaching anoxia, like Culex quinquefasciatus mosquitoes [53]. These findings are consistent with reports of successful Ae.…”
Section: Discussionsupporting
confidence: 88%
“…The availability of sufficient water of a reliable quality is an essential requirement for mosquito mass rearing in support of SIT programmes and others relying on large-scale production of mosquitoes. An extensive literature exists describing the characteristics of mosquito larval habitats in nature (e.g., [ 33 – 36 ]). Every Anopheles species has its preferred water bodies for oviposition, depending on climate, physical geography and human activities, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae complex. Anopheles coluzzii was found cohabiting with Culex species in choke gutters and other organically polluted habitats [ 36 ], and it is reported that in some West African cities in the savanna, An. arabiensis has developed the ability to breed in larval habitats contaminated by waste waters [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of ammonia nitrogen was lower and this might be the result of the transfer of volatile and semi volatile compounds (ammonia) from water bodies to the atmosphere (Schindler, 2001). The amount of ammonium concentration was low as compared to finding report by Kudom (2015). The small amount of ammonium concentration in the habitat of larvae suggests that larval excretion of NH 4 + was being balanced by its removal through microbial metabolism.…”
Section: Discussionmentioning
confidence: 71%